2003
DOI: 10.1080/00288306.2003.9515011
|View full text |Cite
|
Sign up to set email alerts
|

The Cretaceous/Tertiary boundary event in New Zealand: Profiling mass extinction

Abstract: Of over 20 known Cretaceous/Tertiary (K/T) boundary sections in the New Zealand region, 6 in the northern South Island were selected for detailed biostratigraphic and paleoenvironmental study because of their apparent stratigraphic completeness and the range of depositional environments represented. These sections represent the only known southern high-latitude (55-60°S) transect of the K/T boundary transition from continental slope to terrestrial mire.The K/T boundary is marked by deposition of an impact fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
1
17
0
1
Order By: Relevance
“…For the southwest Pacific, a pattern of short-lived climate instability followed by prolonged climatic cooling over ~1 Myrs has been inferred from both marine and terrestrial K/Pg boundary records (Vajda et al, 2001;Hollis, 2003;Vajda and Raine, 2003). Prolonged cooling has been invoked to explain both a delayed recovery of calcareous plankton and the abundance of diatoms and radiolarians in the basal Paleocene pelagic sediments of northeastern South Island, New Zealand (Hollis et al, 1995(Hollis et al, , 2003a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the southwest Pacific, a pattern of short-lived climate instability followed by prolonged climatic cooling over ~1 Myrs has been inferred from both marine and terrestrial K/Pg boundary records (Vajda et al, 2001;Hollis, 2003;Vajda and Raine, 2003). Prolonged cooling has been invoked to explain both a delayed recovery of calcareous plankton and the abundance of diatoms and radiolarians in the basal Paleocene pelagic sediments of northeastern South Island, New Zealand (Hollis et al, 1995(Hollis et al, , 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…1) contains the most complete known K/Pg transition in a neritic setting in the South Pacific region (Hollis and Strong, 2003). It provides an important link between bathyal marine and terrestrial sections in New Zealand (Hollis, 2003) and is one of only two neritic K/Pg boundary record in the Southern Hemisphere, the other being on Seymour Island, Antarctic Peninsula (Elliot et al, 1994;Bowman et al, 2012;Kemp et al, 2014;Petersen et al, 2016;Witts et al, 2016). The mid-Waipara section contains abundant and diverse palynomorphs, including dinoflagellates Willumsen, 2004;2006;2012;Ferrow et al, 2011) and terrestrial palynomorphs (Vadja et al, 2001;Vadja and Raine, 2003;Ferrow et al, 2011), which provide qualitative indications of climatic and environmental variability.…”
Section: Introductionmentioning
confidence: 99%
“…Lithologies such as organic-rich mudstone and soft calcareous mudstone or marl tend to yield slightly to strongly negative bulk carbonate δ 13 C values , which result from diagenetic interaction with isotopically light organic matter, either in situ or carried in pore waters (Marshall 1992;Schmitz et al 1997a). In all Muzzle Group lithologies examined so far, bulk carbonate δ 18 O bears a diagenetic overprint that makes paleoenvironmental interpretation very difficult to impossible (Hollis 2003;Hollis et al 2003). Bulk carbonate δ…”
Section: Carbon Isotope Stratigraphymentioning
confidence: 99%
“…Previous stratigraphic studies of Muzzle Group lithologies (Hancock et al 2003;Hollis et al 2003 have shown that stable isotope analysis of bulk carbonate from indurated limestone yields δ 13 C profiles that can be correlated with some confidence to global deep sea δ 13 C records (e.g., Zachos et al 2001). Lithologies such as organic-rich mudstone and soft calcareous mudstone or marl tend to yield slightly to strongly negative bulk carbonate δ 13 C values , which result from diagenetic interaction with isotopically light organic matter, either in situ or carried in pore waters (Marshall 1992;Schmitz et al 1997a).…”
Section: Carbon Isotope Stratigraphymentioning
confidence: 99%
“…Secondly, apparent turnover may be exaggerated by monographic effects inasmuch as many studies have tended to extend up to, but not across, the boundary (e.g., Roncaglia et al, 1999; but see Willumsen, 2000). Thirdly, the Cretaceous-Paleocene boundary is known to correspond to an unconformity in many or most New Zealand sections (Hollis, 2003). Finally, event levels in the composite are relatively widely spaced around the Cretaceous-Paleocene boundary, and, thus, for the reasons outlined above, the size of the cluster is likely to be exaggerated (compare Figs.…”
Section: Identifi Cation Of "Global" Event Clustersmentioning
confidence: 99%